Impact of type of reduced‐intensity conditioning regimen on the outcomes of allogeneic haematopoietic cell transplantation in classical Hodgkin lymphoma. (21st April 2020) - Ahmed, Sairah; Ghosh, Nilanjan; Ahn, Kwang W.; Khanal, Manoj; Litovich, Carlos; Mussetti, Alberto; Chhabra, Saurabh; Cairo, Mitchell; Mei, Matthew; William, Basem; Nathan, Sunita; Bejanyan, Nelli; et al.
Summary: Reduced‐intensity conditioning (RIC) allogeneic haematopoietic cell transplantation (allo‐HCT) is a curative option for select relapsed/refractory Hodgkin lymphoma (HL) patients; however, there are sparse data to support superiority of any particular conditioning regimen. We analyzed 492 adult patients undergoing human leucocyte antigen (HLA)‐matched sibling or unrelated donor allo‐HCT for HL between 2008 and 2016, utilizing RIC with either fludarabine/busulfan (Flu/Bu), fludarabine/melphalan (Flu/Mel140) or fludarabine/cyclophosphamide (Flu/Cy). Multivariable regression analysis was performed using a significance level of <0·01. There were no significant differences between regimens in risk for non‐relapse mortality (NRM) ( P  = 0·54), relapse/progression ( P  = 0·02) or progression‐free survival (PFS) ( P  = 0·14). Flu/Cy conditioning was associated with decreased risk of mortality in the first 11 months after allo‐HCT (HR = 0·28; 95% CI = 0·10–0·73; P  = 0·009), but beyond 11 months post allo‐HCT it was associated with a significantly higher risk of mortality, (HR = 2·46; 95% CI = 0·1.32–4·61; P  = 0·005). Four‐year adjusted overall survival (OS) was similar across regimens at 62% for Flu/Bu, 59% for Flu/Mel140 and 55% for Flu/Cy ( P  = 0·64), respectively. These data confirm the choice of RIC for allo‐HCT in HL does not influence risk of relapse, NRM or PFS. Although no OS benefit was seen between Flu/Bu and Flu/Mel 140; Flu/Cy was associated with a significantly higher risk of mortality beyond 11 months from allo‐HCT (possibly due to late NRM events).